Outdoor tourism demand segmentation: a case study from north of Portugal - Scalabrini, Elaine (2022)
This research aimed to segment the market of visitors who practise outdoor activities in the North region of Portugal based on their motivations. An online survey was conducted between June to September of 2021, with a sample of 200 tourists who realised the region's outdoor activities during this period. The data collected allowed determining factor analysis and the clusters. Two factors: services/hospitality and nature experiences, and three clusters: soft practitioners, radicals, and enthusiasts were delimited. The results show that these groups differ in motivations and practised activities. Segmentation of outdoor tourism demand in North of Portugal should set out marketing and promotion strategies in different destinations, attracting demand from outside the region, and according to their preferences.